Cost and quality of life analysis of HIV self-testing and facility-based HIV testing and counselling in Blantyre, Malawi - Maheswaran, H; Petrou, S; Macpherson, P; Choko, A; Kumwenda, F; Lalloo, D; Clarke, A; Corbett, E (BioMed Central, 2016)
Background HIV self-testing (HIVST) has been found to be highly effective, but no cost analysis has been undertaken to guide the design of affordable and scalable implementation strategies. Methods Consecutive HIV self-testers and facility-based testers were recruited from participants in a community cluster-randomised trial (ISRCTN02004005) investigating the impact of offering HIVST in addition to facility-based HIV testing and counselling (HTC). Primary costing studies were undertaken of the HIVST service and of health facilities providing HTC to the trial population. Costs were adjusted to 2014 USD and INT$. Recruited participants were asked about direct non-medical and indirect costs associated with accessing either modality of HIV testing, and additionally their health-related quality of life was measured using the EuroQol EQ-5D. Results A total of 1,241 participants underwent either HIVST (n = 775) or facility-based HTC (n = 446). The mean societal cost per participant tested through HIVST (USD9.23; 95 % CI: USD9.14-USD9.32) was lower than through facility-based HTC (USD11.84; 95 % CI: USD10.81-12.86). Although the mean health provider cost per participant tested through HIVST (USD8.78) was comparable to facility-based HTC (range: USD7.53-USD10.57), the associated mean direct non-medical and indirect cost was lower (USD2.93; 95 % CI: USD1.90-USD3.96). The mean health provider cost per HIV positive participant identified through HIVST was higher (USD97.50) than for health facilities (range: USD25.18-USD76.14), as was the mean cost per HIV positive individual assessed for anti-retroviral treatment (ART) eligibility and the mean cost per HIV positive individual initiated onto ART. In comparison to the facility-testing group, the adjusted mean EQ-5D utility score was 0.046 (95 % CI: 0.022-0.070) higher in the HIVST group. Conclusions HIVST reduces the economic burden on clients, but is a costlier strategy for the health provider aiming to identify HIV positive individuals for treatment. The provider cost of HIVST could be substantially lower under less restrictive distribution models, or if costs of oral fluid HIV test kits become comparable to finger-prick kits used in health facilities.